Reason for visit to dentist following trauma to primary teeth-A one- year Retrospective study - PRASANNA, S.G. VISHNU; GURUNATHAN, DEEPA; DINESH, SARAVANA (The journal of contemporary issues in business and government, 2020)
Aim of the study is to identify the clinical cases related to trauma to primary dentition visiting saveetha dental hospital. Traumatic injuries to primary teeth are second most frequent cause of consultation in pediatric dental practice. The most commonly affected primary teeth are upper central incisors and more than one tooth can be lesioned. Evaluation of patients who reported to saveetha dental hospital with trauma to primary teeth. Data was collected from DIAS software. Results were statistically analysed with SPSS software. Mobile tooth was the most common reason for visit to dentist following trauma to primary teeth. Also males in the age group of 5-7 reported more common. The highest prevalence among trauma to primary teeth was more common in age group 5-7 years with a male predominance and most common reason for visit to dentist was mobile tooth caused by trauma which were mostly extracted. Chi square test shows p>0.05, not significant.Within the limitations of the study, them highest prevalence among trauma to primary teeth was more common in age group 5-7 years with a male predominance and most common reason for visit to dentist was mobile tooth caused by trauma which were mostly extracted.